Measuring children’s self-efficacy and proxy efficacy related to fruit and vegetable consumption - Geller, Karly S.; Dzewaltowski, David A.; Rosenkranz, Richard R.; Karteroliotis, Konstantinos (My University, 2011)
BACKGROUND:  Social cognitive theory describes self-efficacy and proxy efficacy as influences on fruit and vegetable consumption (FVC). Proxy efficacy was defined as a child’s confidence in his or her skills and abilities to get others to act in one’s interests to provide fruit and vegetable (FV) opportunities. The purpose of this study was to develop a scale assessing children’s self-efficacy and proxy efficacy for FVC at after-school programs and at home. METHODS:  Elementary-aged children (n = 184) attending 7 after-school programs completed a self-efficacy questionnaire relevant to FVC. Questionnaire validity was investigated with exploratory factor analysis and mixed-model analysis of covariance. Internal consistency reliability and readability were also assessed. RESULTS:  The questionnaire assessed 4 constructs: self-efficacy expectations for fruit consumption, self-efficacy expectations for vegetable consumption, proxy efficacy to influence parents to make FV available, and proxy efficacy to influence after-school staff to make FV available. Children perceiving FV opportunities in after-school had greater self-efficacy expectations for FVC and greater proxy efficacy to influence after-school staff compared to students who did not perceive FV opportunities. Children attending schools of higher socioeconomic status (SES) and less diversity were more confident they could influence their parents to make FV available than students attending lower SES and less diverse schools. Adequate internal consistency and test-retest reliabilities were established. CONCLUSIONS:  Self-efficacy is a multicomponent construct that can be assessed in children using the reliable and valid instrument evaluated by the current study.
Keywords: Nutrition and diet; After-school; Self-efficacy; Fruits and vegetables